Analysis of the dynamic characteristics of the coupling relationship between urbanization and environment in Kunming city, southwest China - Dongmei Lei; Xiaoyong Xu; Yuan Zhang (Cleaner Environmental Systems, 2021)
Urbanization are resulting in enormous environment pressure to China's plateau cities. Taking Kunming as an example, based on statistical data from 2000 to 2016, this paper evaluated the comprehensive level of urbanization and environment by using the index system construction method, and investigated the dynamic changes of the coupling relationship between urbanization and environment by using the coupling coordination degree model. An index system for assessment of the comprehensive level of urbanization is established based on four aspects (social, economic, demographic and spatial urbanization). An index system of the comprehensive level of environment was also presented based on three aspects (response, state and pressure environment). The results show that: (1) In urbanization sub-system, the weight of social urbanization is the highest. While in environment sub-system, environment response has the highest weight. These indicate that these two are the key factors that need to be prioritized in the decision-making of adjustment and coordinated development. (2) During the past 16 years, the comprehensive level of urbanization increased rapidly from 0.117 to 0.909, while that of environment only increased from 0.446 to 0.566, showing a fluctuating trend. These represent that the process of environment change in the plateau region is complex and unstable. And the long-term environment improvement and management measures, such as controlling sewage discharge and improving water environment, need to be implemented. (3) The index of coupling coordination degree increased from 0.338 to 0.599, showing a S-shaped curve. Kunming had experienced a transformation from “moderately unbalanced development with hindered urbanization” to “preliminarily balanced development with a lagging environment”, which denotes that compared with the development of economic and social, the environment protection of plateau cities is lagging behind. This empirical analysis of Kunming indicate that CCD model is very useful for comprehensively quantifying the relationships between urbanization and the environment, and can produce objective results of great significance and reference value for Kunming's future development.